Climate-Driven Shifts in Vector-Borne Disease Ecology Across South Asia - Atul Khajuria; Stephen Monday; Eric Kwasi Elliason; Gagan; J. Samuel Kamanda (International Journal of Insects, 2025)
Climate change remains one of the most important phenomena affecting the geographical distribution and movement patterns of vector-borne diseases. In South Asia – characterized by high population density, rich biodiversity, and sharp climatic differences – there is growing evidence of the relationship between increasing temperatures and erratic precipitation, along with the behavior of insect vectors. This research aims to evaluate the effects of climate environmental changes on the distribution and seasonal activity of important vector insects like Aedes aegypti, Anopheles stephensi, Phlebotomus argentipes, and tick species. A systematic review of epidemiological literature along with climate data and vector monitoring data from 2010–2024 were analyzed using spatial analysis through geoinformatics. There is striking contemporaneous evidence of both longitudinal and vertical shifts in the habitats of some vectors, and now many more disease-carrying species are being reported from regions which were earlier considered non-endemic, like the Himalayan foothills and the semiarid plains. Much of these newly affected documented areas are gradually facing increased cases of dengue, malaria, and leishmaniasis. Most of the pathogen incubation periods in the vectors has reduced due to the rise in temperatures, while the prolonged precipitation and humidity levels have aided in higher breeding and better survival of the vectors. The study emphasizes the importance of focused climate change public health strategies, responsive multisectoral vector monitoring, and geo-specific anticipatory frameworks, including preemptive climate-adaptable measures aimed at the vulnerable population groups. It draws attention toward the need for transnational collaboration, enhanced infrastructure, and public health information systems to address the rising danger associated with climate-sensitive vector-borne diseases in South Asia. These observations will help guide policymakers, public health experts, and researchers formulate effective plans for long-term preventive measures
Keywords: Climate change; Environmental Health; South Asia; disease transmission; insect vectors; mosquitoes; vector-borne diseases